Metabolic flux analysis of carbon balance in Lactobacillus strains. (21st September 2016) - Zhang, Yixing; Zeng, Fan; Hohn, Keith; Vadlani, Praveen V.
Abstract : Metabolic flux analyses were performed based on the carbon balance of six different Lactobacillus strains used in this study. Results confirmed that L. delbrueckii, L. plantarum ATCC 21028, L. plantarum NCIMB 8826 Δ ldhL1, L. plantarum NCIMB 8826 Δ ldhL1 ‐pCU‐P xylAB, and L. plantarum NCIMB 8826 Δ ldhL1 ‐pLEM415‐ xylAB metabolized glucose via EMP: whereas, L. brevis metabolized glucose via PK pathway. Xylose was metabolized through the PK pathway in L. brevis, L. plantarum NCIMB 8826 Δ ldhL1 ‐pCU‐P xylAB and L. plantarum NCIMB 8826 Δ ldhL1 ‐pLEM415‐ xylAB . Operation of both EMP and PK pathways was found in L. brevis, L. plantarum NCIMB 8826 Δ ldhL1 ‐pCU‐P xylAB, and L. plantarum NCIMB 8826 Δ ldhL1 ‐pLEM415‐ xylAB when glucose plus xylose were used as carbon source. The information of detailed carbon flow may help the strain and biomass selection in a designed process of lactic acid biosynthesis. © 2016 American Institute of Chemical Engineers Biotechnol. Prog ., 32:1397–1403, 2016